Waking, Dreaming, Being Self and Consciousness in Neuroscience, Meditation, and Philosophy. - Thompson, Evan. (New York : Columbia University Press, 2014)
A renowned philosopher of the mind, also known for his groundbreaking work on Buddhism and cognitive science, Evan Thompson combines the latest neuroscience research on sleep, dreaming, and meditation with Indian and Western philosophy of the mind, casting new light on the self and its relation to the brain. Thompson shows how the self is a changing process, not a static thing. When we are awake we identify with our body, but if we let our mind wander or daydream, we project a mentally imagined self into the remembered past or anticipated future. As we fall asleep, the impression of being a.
Table of Contents; Foreword by Stephen Batchelor; Prologue: The Dalai Lama's Conjecture; Acknowledgments; Introduction; 1. Seeing: What Is Consciousness?; 2. Waking: How Do We Perceive?; 3. Being: What Is Pure Awareness?; 4. Dreaming: Who Am I?; 5. Witnessing: Is This a Dream?; 6. Imagining: Are We Real?; 7. Floating: Where Am I?; 8. Sleeping: Are We Conscious in Deep Sleep?; 9. Dying: What Happens When We Die?; 10. Knowing: Is the Self an Illusion?; Notes; Bibliography; Index
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Consciousness; Self; Consciousness; Self; PHILOSOPHY / Movements / Humanism; Electronic books